PENGARUH MEDIA PEMBELAJARAN RODA PINTAR TERHADAP MOTIVASI DAN PEMAHAMAN SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI UPTD SDN PEJAGAN 1 BANGKALAN - Mahbubi, Roihan; Arifin, Zainal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Student motivation and comprehension are essential in the learning process. The purpose of this study is to determine the effect of the Smart Wheel learning media on motivation and comprehension in the Indonesian language subject focused on reading aloud. The design used is a pretest-posttest pre-experimental design, specifically a one-group pretest-posttest design. The dependent variables are student motivation and comprehension. Data on student motivation and comprehension were obtained from test results. The test instruments were developed based on indicators of student motivation and comprehension. Hypothesis testing in this study was conducted using the paired sample t-test. The results showed a significant value (p) = 0.000 < 0.05, indicating that the Smart Wheel learning media has a significant effect on student motivation and comprehension in the Indonesian language subject.